Quantitative Evaluation of Brain Echogenicity in Hypoxic-Ischemic Encephalopathy in Term Neonates Compared with Controls - Gonçalves, Fabrício Guimarães; Freeman, Colbey; Khrichenko, Dmitry; Hwang, Misun (Ultrasound International Open, 2022)
Purpose Neurosonography evaluation of neonatal hypoxic-ischemic encephalopathy (HIE) is mainly qualitative. We aimed to quantitatively compare the echogenicity of several brain regions in patients with HIE to healthy controls.Materials and Methods 20 term neonates with clinical/MRI evidence of HIE and 20 term healthy neonates were evaluated. Seven brain regions were assessed [frontal, parietal, occipital, and perirolandic white matter (WM), caudate nucleus head, lentiform nucleus, and thalamus]. The echogenicity of the calvarial bones (bone) and the choroid plexus (CP) was used for ratio calculation. Differences in the ratios were determined between neonates with HIE and controls.Results Ratios were significantly higher for HIE neonates in each region (p<0.05). The differences were greatest for the perirolandic WM, with CP and bone ratios being 0.23 and 0.22 greater, respectively, for the HIE compared to the healthy neonates (p<0.001). The perirolandic WM had a high AUC, at 0.980 for both the CP and bone ratios. The intra-observer reliability for all ratios was high, with the caudate to bone ratio being the lowest at 0.832 and the anterior WM to CP ratio being the highest at 0.992.Conclusion When coupled with internal controls, quantitative neurosonography represents a potential tool to identify early neonatal HIE changes. Larger cohort studies could reveal whether a quantitative approach can discern between degrees of severity of HIE. Future neurosonography protocols should be tailored to evaluate the perirolandic region, which requires posterior coronal scanning.
Keywords: brain; areas; structures & systems; ultrasound; methods & techniques; hypoxia; themes